2018
DOI: 10.5530/pj.2018.3.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gynura procumbens Extracts on Anti-Proliferative Activity and its Associated Morphological Changes of Human Glioblastoma multiforme Cell Line (U-87)

Abstract: Objective: Gynura procumbens (Lour.) Merr is a well-known traditional herb and is widely used for traditional medicine by human. Previous clinical studies have shown the benefit effect of this leaves with inflammation, high blood pressure and others. This study aims to investigate the effect of methanol, ethanol, and ethyl acetate extracts of Gynura procumbens on U-87 cell line, human Glioblastoma multiforme cell line. Methods: In the present study, effect of methanol, ethanol and ethyl acetate extracts on U-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Meanwhile, RSR, after 30 days of transplanting, started to grow slowly. This result parallels Qi et al 13 's findings, which reported that plants allocated more biomass to roots in the seedling stage or due to climatic conditions, soil fertility, and management practices 5,43,44 . Results of the present experiments showed that the highest net photosynthetic rate of G. procumbens was 13.89 µmol m -2 s -1 at 30% shade than 12.38 µmol m -2 s -1 at 0% shade (full sunlight) (Table 1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, RSR, after 30 days of transplanting, started to grow slowly. This result parallels Qi et al 13 's findings, which reported that plants allocated more biomass to roots in the seedling stage or due to climatic conditions, soil fertility, and management practices 5,43,44 . Results of the present experiments showed that the highest net photosynthetic rate of G. procumbens was 13.89 µmol m -2 s -1 at 30% shade than 12.38 µmol m -2 s -1 at 0% shade (full sunlight) (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…It is widely distributed in Africa 1,2 and tropical regions of Southeast Asia and China 3,4 . Non-toxic leaves have extensive pharmacological properties, including anti-diabetic, anti-hypertensive, antioxidant, and vasorelaxant activity 5 . The medicinal benefits of G. procumbens are related to its bioactive compounds, such as saponins, flavonoids, and terpenoids 4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Merr locally known as “pokok sambung nyawa” is commonly found in Malaysia, Indonesia, Thailand, Vietnam, and China. It is traditionally used to treat various diseases including fever, rashes, constipation, kidney disease, and cancer [17, 18]. Previous pharmacological studies have shown that G. procumbens possesses anti-inflammatory, antihypertensive, antihyperlipidaemic, antioxidative, and cardioprotective properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28]. Among these plants, Gynura procumbens is an extraordinary herb widely available in the southeast region of the world, such as Thailand, Malaysia, China, Vietnam, Bangladesh, and Indonesia [29]. It is a small (around 1-3 m long) flowering plant that belongs to the Asteraceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the most recent revelation of the antioxidant properties of this plant gives a clear and precise idea to treat various diseases by reducing free radical production [33,[43][44][45][46][47]. For this reason, the Chinese name of this plant is "Pokok Sambung Nyawa," the meaning of which is "prolongation of life" [37,48]. Furthermore, certain findings have provided significant evidence demonstrating the promising hepatoprotective potentials of G. procumbens, which has piqued the interest of researchers to investigate further the protective effects of G. procumbens against specific types of hepatotoxicity [24,49].…”
Section: Introductionmentioning
confidence: 99%